2016
DOI: 10.1111/rec.12449
|View full text |Cite
|
Sign up to set email alerts
|

Oyster reef restoration: substrate suitability may depend on specific restoration goals

Abstract: A limited supply of oyster shell for restoration practices has prompted investigations of alternative substrates used in construction of artificial oyster reefs. The success of oyster reef restoration projects is increasingly focused not only on oyster densities, but also on habitat provisioning for associated fauna. A subtidal oyster reef complex (0.24 km2) was restored in the Mission‐Aransas Estuary, Texas, U.S.A., in July 2013 using replicated mounds of concrete, limestone, river rock, and oyster shell subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 69 publications
1
19
2
Order By: Relevance
“…At present, erosion is an increasing problem along coastlines in general, and at degraded sites that require restoration in particular 36 . To combat this pervasive challenge, hard structures from shells or concrete are often applied to provide stable substrates necessary to stimulate reef formation [37][38][39][40][41][42][43] , while sediment stabilization measures have been used to support vegetation establishment 44,45 . Our approach builds upon these efforts by experimentally demonstrating that tailor-made mimicry of species-specific key emergent traits-identified from past ecological studies-facilitates the establishment of different habitat-forming species.…”
Section: Discussionmentioning
confidence: 99%
“…At present, erosion is an increasing problem along coastlines in general, and at degraded sites that require restoration in particular 36 . To combat this pervasive challenge, hard structures from shells or concrete are often applied to provide stable substrates necessary to stimulate reef formation [37][38][39][40][41][42][43] , while sediment stabilization measures have been used to support vegetation establishment 44,45 . Our approach builds upon these efforts by experimentally demonstrating that tailor-made mimicry of species-specific key emergent traits-identified from past ecological studies-facilitates the establishment of different habitat-forming species.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, densities were 2× higher than on the reportedly largest reestablished metapopulation of oysters globally (overall mean: 1027 ± 52 n/m 2 in a Chesapeake Bay sub‐estuary; Schulte et al ). In the Gulf of Mexico, Graham et al () reported mean oyster densities of 1,023 and 939 n/m 2 on restored reefs constructed using concrete and limestone substrates, respectively. In a related study, short‐term (4 month) field deployments of substrates resulted in spat densities of 1,242–1,513 and 929–1,447 n/m 2 on concrete and limestone, respectively (George et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Limestone and concrete have been demonstrated as successful substrates for oyster reef restoration along the U.S. Gulf and Atlantic coasts (Soniat et al1991; Soniat & Burton ; Brumbaugh ; LDWF ; George et al 2015; Graham et al ). In the current study, substrate type was not an important factor influencing oyster population development or faunal community composition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A substitution of 20% of the aggregates (D4/10) by oyster shell aggregates was made to study the effect of this biomineral by-product on the recruitment of oyster larvae. Indeed, the incorporation of mollusc shell aggregates can increase the bioreceptivity of concrete because they provide an ideal substrate for the settlement of marine organisms (Graham et al, 2017;Hanlon et al, 2018). After the characterization of the raw materials, concrete mix designs formulation was carried out in accordance with EN 206-1.…”
Section: Concrete's Formulationsmentioning
confidence: 99%